Studi Kestabilan Sistem dan Pelepasan Beban (Load Shedding) Berdasarkan Standar IEEE di PT. Pertamina (Persero) Refinery Unit IV - Nuswantara, N.; Ariastina, W.G.; Amrita, A. A. N. (Jurnal SPEKTRUM; Vol 4 No 1 (2017): Jurnal SPEKTRUM, 2017)
The study intends to explain the shortage of PT.Pertamina RU IV’s SOP in order to overcome generator’s instability during breakdown. The observation found that the problem occured due to PT. Pertamina RU IV policy to conduct the load shedding performance manually or with UFR (Under Frequency Relay) support to overcome breakdown. However this procedure came with some shortages. One of them was the standard procedure which has not met global IEEE standard yet and it took time to stabilize the system. Therefore to solve this problem, the IEEE standard imposed to be applied as a basic procedure. It showed the used of IEEE standard was more effective to overcome the system instability in PT. Pertamina RU IV because the study shows, the IEEE procedure could stabilized the system to 99,85% in 23 seconds, 98,5% in 8 seconds, 99,16% in 40 seconds and to 98,48% in 70 seconds on 4 different study cases. Keywords: IEEE Standard , Load shedding, PT. Pertamina (Persero) RU IV, Stability.